2015
DOI: 10.1093/mnras/stv694
|View full text |Cite
|
Sign up to set email alerts
|

Supermassive black hole formation at high redshifts via direct collapse in a cosmological context

Abstract: We study the early stage of the formation of seed supermassive black holes via direct collapse in dark matter (DM) halos, in the cosmological context. We perform highresolution zoom-in simulations of such collapse at high-z. Using the adaptive mesh refinement code ENZO, we resolve the formation and growth of a DM halo, until its virial temperature reaches ∼ 10 4 K, atomic cooling turns on, and collapse ensues. We demonstrate that direct collapse proceeds in two stages, although they are not well separated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 84 publications
1
59
1
Order By: Relevance
“…We use fully cosmological initial conditions (ICs) for our models and invoke zoom-in simulations (e.g. Choi et al 2015;Luo et al 2016;Shlosman et al 2016;Luo et al 2018;Ardaneh et al 2018).…”
Section: Initial Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…We use fully cosmological initial conditions (ICs) for our models and invoke zoom-in simulations (e.g. Choi et al 2015;Luo et al 2016;Shlosman et al 2016;Luo et al 2018;Ardaneh et al 2018).…”
Section: Initial Conditionsmentioning
confidence: 99%
“…Otherwise, the H 2 cooling can lead to fragmentation and formation of Pop III stars, thus preventing formation of a massive central black hole seed (Haiman et al 2000;Wise & Abel 2008;Begelman & Shlosman 2009;Regan & Haehnelt 2009;Greif et al 2011;Latif et al 2016;Regan & Downes 2018). Numerical simulations of an optically-thin collapse have confirmed that in the absence of a molecular cooling, the gas stays isothermal, at the atomic hydrogen cooling floor (Omukai 2001;Bromm & Loeb 2003;Shang et al 2010;Choi et al 2013Choi et al , 2015Latif et al 2013;Choi et al 2013;Latif et al 2016;Shlosman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Runaway collapse of this gas can lead to the formation of a seed BH in the nuclear regions that can retain up to 90% of the Jeans mass (see e.g. Begelman et al 2006;Regan & Haehnelt 2009;Latif et al 2013;Choi et al 2014). Most relevant to the final assembly of DCBHs are then the chemical pathways that involve the formation and destruction of molecular hydrogen in their host haloes.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous numerical experiments have been performed to study the direct collapse scenario and show that in the presence of an intense LW flux the formation of molecular hydrogen remains suppressed and the collapse occurs isothermally with T ∼ 8000 K (Bromm & Loeb 2003;Wise et al 2008;Regan & Haehnelt 2009;Latif et al 2013a;Prieto et al 2013;Choi et al 2015;Becerra et al 2015). Moreover, these simulations demonstrate that fragmentation occurs occasionally but large inflow rates of about 0.1−1 M ⊙ /yr are available to grow massive objects in these conditions.…”
Section: Introductionmentioning
confidence: 99%